Serum Titers of Acute Phase Proteins and Immunoglobulin Classes in Nigerian Cigarette Smokers (Tanzania Medical Journal, 2008)
Background: Smoking remains the cause of preventable death but the cause(s) of adverse effect(s) of cigarette smoking is yet to be completely revealed.Objectives: To determine the levels of immunoglobulin classes (IgG, A and M) and acute phase proteins (alpha 2-macroglobulin, transferrin and caeruloplasmin) in 13 Nigerian male cigarette smokers and 14 non – smokers as control by single radial immuno-diffusion method. Methods: Immuno-diffusion method was used to determine the levels of immunoglobulin classes and acute phase proteins. Setting: Students and staff of University of Ibadan, Nigeria. Results: The mean levels of IgM, transferrin and alpha 2-macroglobulin were significantly raised while IgA, IgG and caeruloplasmin were not significantly raised in cigarette smokers compared with the control. There were no significant correlation between duration of smoking, nicotine inhaled, and tar inhaled with any of the humoral factors.Conclusion: This study detected abnormalities in certain aspects of humoral immune responses in Nigerian smokers and this could lead to development of auto-antibodies and cardiovascular diseases in long time cigarette smokers. Tanzania Medical Journal Vol. 23 (1) 2008: pp. 5-7